Vitamin D level as a predictor of pneumonia and asthma in children less than 5 years of age - Sharma, Neha; Sethi, Anuj Shamsher; Sethi, R. S. (International Journal of Contemporary Pediatrics, 2020)
Background: Childhood pneumonia is a global health problem .It the leading cause of death for children under the age of five years. 95% of all pneumonia cases under the age of five occurs in developing countries. Asthma remains the most common chronic disease of childhood in the world. The observation that vitamin D deficiency and asthma share risk factors such as urban residence, obesity and African American ethnicity has generated interest in exploring a link between these two conditions. This study was taken up to assess the role of vitamin D as a predictor of pneumonia and asthma in children less than 5 years of age. Methods: A prospective observational case control study was conducted in MLB Medical college, Jhansi from January 2015 to December 2016 (1 year 11 months). A total of 60 children including 30 asthma cases, 20 pneumonia cases and 10 controls, aged, 6-60 months were enrolled. Controls were healthy children attending outpatient services for immunization. Results: The mean age of the pneumonia patient was 1.5 years, while mean age in asthma patients was 3.1yrs. Ratio of male and female in pneumonia cases was1.5:1, while is asthma ratio was 2:1. In our study 45% pneumonia cases had deficient level of vitamin D (<20ng/ml) and mean level was 11.08±4.68 while 40% of control had deficient level of vitamin D and mean level was 16.04±1.61, p value was 0.0166 and there was significant difference in both the groups. In Asthma cases 53.33% patient had deficient level of vitamin-D and mean level was 10.62±2.908 as compared to 40% control (mean : 16.04±1.62) ‘p’ value was <0.0001 and was highly significant. Conclusions: Our study has illustrated that vitamin-D levels were significantly low in pneumonia and asthma patients as compared to control.